2012
DOI: 10.1093/ntr/nts099
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco-Specific Nitrosamine Exposures in Smokers and Nonsmokers Exposed to Cigarette or Waterpipe Tobacco Smoke

Abstract: Introduction: The causal relationship between tobacco smoking and a variety of cancers is attributable to the carcinogens that smokers inhale, including tobacco-specifi c nitrosamines (TSNAs). We aimed to assess the exposure to TSNAs in waterpipe smokers (WPS), cigarette smokers (CS), and nonsmoking females exposed to tobacco smoke. Methods:We measured 2 metabolites , 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) and its glucuronides (NNAl-Gluc) in the urine of males who were either current CS or WPS, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 47 publications
5
34
0
Order By: Relevance
“…Levels of NNAL in cigarette smokers in our study were similar to those reported by Jacob et al 12. A recent study comparing NNAL of waterpipe smokers, cigarette smokers, and their non-smoking wives (passively exposed by definition), also detected higher levels of NNAL in cigarette and waterpipe smokers when compared with their wives 19. However, the selection of the non-smoking group (spouses), and the daily smoking frequency of waterpipe smokers (approximately 12 waterpipes/day) in that study limits its generalisability in terms of differentiating exposure gradients between waterpipe smokers and non-smokers 19.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Levels of NNAL in cigarette smokers in our study were similar to those reported by Jacob et al 12. A recent study comparing NNAL of waterpipe smokers, cigarette smokers, and their non-smoking wives (passively exposed by definition), also detected higher levels of NNAL in cigarette and waterpipe smokers when compared with their wives 19. However, the selection of the non-smoking group (spouses), and the daily smoking frequency of waterpipe smokers (approximately 12 waterpipes/day) in that study limits its generalisability in terms of differentiating exposure gradients between waterpipe smokers and non-smokers 19.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study comparing NNAL of waterpipe smokers, cigarette smokers, and their non-smoking wives (passively exposed by definition), also detected higher levels of NNAL in cigarette and waterpipe smokers when compared with their wives 19. However, the selection of the non-smoking group (spouses), and the daily smoking frequency of waterpipe smokers (approximately 12 waterpipes/day) in that study limits its generalisability in terms of differentiating exposure gradients between waterpipe smokers and non-smokers 19. In our study, we recruited the three groups independent of each other; although our recruitment strategy did not guarantee that the enrolled participants were representative of waterpipe, cigarette and non-smokers in the general population.…”
Section: Discussionmentioning
confidence: 88%
“…In comparison, smoking of a full tobacco bowl in a clinical research setting resulted in an average urine NNAL boost of 5 pg/mg creatinine, a ~3-fold greater increase than was observed in the current study (13). NNAL exposure has been shown to be lower when smoking water pipes compared to cigarettes (14), similar to the findings of a cross-sectional study in which lower NNAL was measured in water pipe smokers compared to cigarette smokers in Egypt (34). NNAL, a metabolite of the potent lung carcinogen NNK, is used to characterize systemic exposure to TSNAs.…”
Section: Nicotine Intakesupporting
confidence: 74%
“…12 Studies demonstrated elevated urinary NNAL levels following smoking hookah tobacco; however, levels were lower compared to smoking cigarettes. 13,2124 …”
Section: Introductionmentioning
confidence: 99%